Analisis Faktor-Faktor Yang Menentukan Loyalitas Karyawan Pada Bmt Mitra Mandiri Wonogiri - Andriyani, Sepni, Muhammad Sholahuddin, S.E.,M.Si (2016)
The research aims to analyze the factors that influence loyality of employee in BMT Mitra Mandiri Wonogiri. This research was taken samples all of population amount 82 people. The analysis used multiple regression with classic assumption test. By the test we know that this model have a normal distribution, not found multikolinearity and heterokedastisity in this model. Analysis result demonstrate that founded positive influences and significant between all of consisting of four variable there is compensation, responsibility, disipline and participation as the factors that influence the loyality of employee at BMT Mitra Mandiri Wonogiri. Key words: loyality of employee.